Lymph node metastasis in patients with gastric cancer: a multi-modality, morphologic and functional imaging study - Zhong, Jinman (Am J Transl Res, 2016)
The aim of the study was to investigate the value of computed tomography (CT), magnetic resonance imaging (MRI) and diffusion weighted imaging (DWI) for diagnosing lymph nodes metastasis before treatment in gastric cancer. Eighty-two patients with proven gastric cancer underwent CT, morphological MRI (T2WI) and DWI examinations. Two radiologists independently assessed these images for the presence of lymph nodes involvement. Pathologic findings were considered as “gold standard”. Independent samples t-test was used for the comparisons of short diameters and ADC values between the positive lymph nodes and the negative lymph nodes. Diagnostic accuracy of these three imaging modalities was evaluated by area under the receiver operating characteristics (ROC) curve (AUC). The ADC value of the positive lymph nodes was (1.15 ± 0.01) × 10(-3) mm(2)/s, which was significantly lower than that of the negative lymph nodes (1.48 ± 0.01) × 10(-3) mm(2)/s (t = 18.70, P < 0.0001). The short diameter of the positive lymph nodes (1.54 ± 0.38 cm) was significantly greater than that of the negative lymph nodes (0.95 ± 0.12 mm) (t = 19.03, P < 0.001). The AUC for all imaging modalities combined (0.893) was significantly larger than that for each imaging modality alone (P < 0.05), and the AUC of DWI (0.797) was significantly larger than (P < 0.05) that of morphological MRI (0.733). There was no statistically significant difference between the AUCs of CT and morphological MRI (P = 0.462). In conclusion, CT, MRI and DWI combined present significantly higher accuracy than each imaging modality alone in the detection of lymph nodes involvement.